Game over : how politics has turned the sports world upside down - Zirin, Dave. (New York : New Press, 2013)
"Sportscaster Howard Cosell dubbed it "rule number one of the jockocracy": sports and politics just don't mix. But in Game Over, celebrated alt-sportswriter Dave Zirin proves once and for all that politics has breached the modern sports arena with a vengeance. From the NFL lockout and the role of soccer in the Arab Spring to the Penn State sexual abuse scandals and Tim Tebow's on-field genuflections, this timely and hard-hitting new book from the "conscience of American sportswriting" (The Washington Post) reveals how our most important debates about class, race, religion, sex, and the raw quest for political power are played out both on and off the field. Game Over offers new insights and analysis of headline-grabbing sports controversies, exploring the shady side of the NCAA, the explosive 2011 MLB All-Star Game, and why the Dodgers crashed and burned. It covers the fascinating struggles of gay and lesbian athletes to gain acceptance, female athletes to be more than sex symbols, and athletes everywhere to assert their collective bargaining rights as union members. Zirin also illustrates the ways in which athletes are once again using their exalted platforms to speak out and reclaim sports from the corporate interests that have taken it hostage. In Game Over, he cheers the victories but also reflects on how far we have yet to go. Combining brilliant set pieces with a sobering overview of today's sports scene in Zirin's take-no-prisoners style, Game Over is a must read for anyone, sports fan or not, interested in understanding how sports reflect and shape society--and why the stakes have never been higher"--Publisher information.
Pre-game -- Occupy the sports world -- "You have to be an ultra from within" : soccer and the Arab spring -- Today's World Cup and Olympics : Invictus in reverse -- Zombie teams and zombie owners -- Joe Paterno : death, remembrance, and the wages of sin -- The NCAA's "whiff of the plantation" -- Here come Los Suns -- "Is your underwear flame retardant" : sexuality and sports -- "I'm not your child" : racism today in sports -- Post-game.
Includes bibliographical references and index.
Keywords: Sports -- Political aspects -- United States; Sports -- Social aspects -- United States; Sports -- Political aspects; Sports -- Social aspects; United States